A Mild‐Stimuli‐Responsive Fluorescent Molecular System Enables Multilevel Anti‐Counterfeiting and Highly Adaptable Temperature Monitoring. (28th August 2022) - Hu, Dingfang; Xu, Wenjun; Wang, Gang; Liu, Ke; Wang, Zhaolong; Shi, Qiyuan; Lin, Simin; Liu, Zhongshan; Fang, Yu
Abstract: Smart luminescent materials with tangible and reversible responses to external stimuli have gained popularity for multiple applications. However, impracticable stimuli and less adaptability render them unfit for real‐life applications. Here, a proton competitive binding‐based molecular system is reported, which demonstrates, both in solution and solid state, remarkable responses toward light illumination and temperature variation. Small change in solvent composition could result in remarkable variation in measurable temperature range at least from −80 to 60 °C. Combination of light illumination and temperature change enables multilevel anti‐counterfeiting, as well as construction of easy‐to‐use and high‐resolution liquid thermometers. The key components in the concerned molecular system are a newly designed fluorophore, NI‐CBN, a four‐coordinated boron derivative of naphthalimide (NI), and an organic fluoride salt that is tetrabutylammonium fluoride (TBAF). Reaction between NI‐CBN and TBAF yields a dynamic fluorophore, NI‐CBN‐F, which shows remarkable color change to the stimuli via proton migration between the imine group in NI‐CBN and the fluoride anion of the salt. Such responses enable the aforementioned advanced anti‐counterfeiting and visible temperature monitoring. Abstract : An imine proton‐competitive binding‐based molecular system that depicts remarkable mild‐stimuli (e.g., small temperature change, humidity variation, light illumination) responsiveness with fast and sharp color changes is developed. The excellent stimuli responsiveness promotes to explore the various potential applications in the field of visual temperature sensing and high‐security anti‐counterfeiting.